Taurodontism: A case report of successful treatment of root and crown - Abdolsamadi HR; Nazari Sh; Mirmotalebi F.; Shirinzad M (Tehran University of Medical Sciences, 2006)
Taurodontism is a rare dental anomaly in which the involved tooth has enlarged and elongated body and pulp chamber with apical displacement of the pulpal floor. Endodontic treatment of these teeth is challenging because it requires identifying the number of root canals. A case of bilateral involvement of maxillary first molar teeth is presented. Endodontic treatment of the right maxillary first molar with taurodontism was indicated due to irreversible pulpitis. In this article, we described the procedure of root canal therapy for this case.